Auditory Discrimination of Lexical Stress Patterns in Hearing-Impaired Infants with Cochlear Implants Compared with Normal Hearing: Influence of Acoustic Cues and Listening Experience to the Ambient Language. Issue 2 (March 2016) - Segal, Osnat; Houston, Derek; Kishon-Rabin, Liat
Abstract : Objectives: To assess discrimination of lexical stress pattern in infants with cochlear implant (CI) compared with infants with normal hearing (NH). While criteria for cochlear implantation have expanded to infants as young as 6 months, little is known regarding infants' processing of suprasegmental-prosodic cues which are known to be important for the first stages of language acquisition. Lexical stress is an example of such a cue, which, in hearing infants, has been shown to assist in segmenting words from fluent speech and in distinguishing between words that differ only the stress pattern. To date, however, there are no data on the ability of infants with CIs to perceive lexical stress. Such information will provide insight to the speech characteristics that are available to these infants in their first steps of language acquisition. This is of particular interest given the known limitations that the CI device has in transmitting speech information that is mediated by changes in fundamental frequency. Design: Two groups of infants participated in this study. The first group included 20 profoundly hearing-impaired infants with CI, 12 to 33 months old, implanted under the age of 2.5 years (median age of implantation = 14.5 months), with 1 to 6 months of CI use (mean = 2.7 months) and no known additional problems. The second group of infants included 48 NH infants, 11 to 14 months old with normal development and no known risk factors for developmental delays. Infants were tested on their ability to discriminate between nonsense words that differed on their stress pattern only (/ dóti / versus / dotí / and / dotí / versus /dóti /) using the visual habituation procedure. The measure for discrimination was the change in looking time between the last habituation trial (e.g., / dóti /) and the novel trial (e.g., / dotí /). Results: (1) Infants with CI showed discrimination between lexical stress pattern with only limited auditory experience with their implant device, (2) discrimination of stress patterns in infants with CI was reduced compared with that of infants with NH, (3) both groups showed directional asymmetry in discrimination, that is, increased discrimination from the uncommon to the common stress pattern in Hebrew (/ dóti / versus / dotí /) compared with the reversed condition. Conclusions: The CI device transmitted sufficient acoustic information (amplitude, duration, and fundamental frequency) to allow discrimination between stress patterns in young hearing-impaired infants with CI. The present pattern of results is in support of a discrimination model in which both auditory capabilities and "top–down" interactions are involved. That is, the CI infants detected changes between stressed and unstressed syllables after which they developed a bias for the more common weak–strong stress pattern in Hebrew. The latter suggests that infants with CI were able to extract the statistical distribution of stress patterns by listening to the ambient language even after limited auditory experience with the CI device. To conclude, in relation to processing of lexical stress patterns, infants with CI followed similar developmental milestones as hearing infants thus establishing important prerequisites for early language acquisition. Abstract : The present study provides evidence that hearing-impaired infants with cochlear implants are able to perceive relevant acoustic information for discriminating between nonsense words that differ only in their lexical stress pattern and that this discrimination is asymmetrical. That is, there is increased discrimination from the uncommon to the common stress pattern in Hebrew compared with the reversed condition. This suggests that infants with cochlear implants were able to extract the statistical distribution of stress patterns by listening to the ambient language, supporting a discrimination model in which both auditory capabilities and "top-down" interactions are involved. Thus, in relation to processing of lexical stress patterns, infants with cochlear implants followed similar developmental milestones as hearing infants, thus establishing important prerequisites for early language acquisition.Supplemental Digital Content is available in the text.